Structural design and mechanism analysis of palm oil harvester - M.A. Yusuff; K.S.M. Wong; K.A. Zakaria; M.N. Sudin; N.M. Daud (Penerbit Universiti Kebangsaan Malaysia, 2024)
Plantation of palm oil in Malaysia is one of the top contributor of the economy. In order to match the supply of palm oil fruit with demand, different harvesting methods are used such as the existing motorized cutter. Although it can reduce the harvesting time and the number of labors involved in harvesting process, the tight arrangement of oil palm fronds and long manually adjusted harvesting pole may cause the inconvenient to the labors. Therefore, this project studies the design of a circular cutter and automatically adjusted telescopic pole with rotational mechanism. The concept development of harvester is based on the scientific study on the limitations, customer requirement and engineering characteristics of existing harvesters. It is followed with the selection of best design of harvester that can solve the problems that faced by labors in existing harvester. The analysis of rotational speed, deflection and bending moment for different components in the palm oil harvester. The design of harvester is done with the aid of CAD software in form of part detail design, orthographic view and exploded view. With the rotational cutting mechanism, the harvester can easily reach and harvest the oil palm fresh fruit bunches from the bottom of the bunches.